Pengaruh Frekuensi Iklan Digital Shopee terhadap Sikap Konsumen dengan Promosi sebagai Variabel Mediasi pada Pengguna Media Sosial TikTok: Studi Kasus Gen Z di Tasikmalaya - Neng Aisah; Isyana Rahayu (CV. ALIM'SPUBLISHING, 2026)
The development of the internet and social media has encouraged e-commerce companies to utilize digital platforms as a marketing tool, one of which is Shopee through TikTok social media. The high frequency of digital advertising is thought to influence consumer attitudes, especially among Generation Z as active TikTok users. To determine the impact of Shopee's digital advertising frequency on consumer attitudes using promotions as a mediating variable on Generation Z TikTok social media users in Tasikmalaya, this study employed quantitative, descriptive, and verification techniques. A total of 100 respondents were sampled using purposive sampling techniques. An online questionnaire with a Likert scale of 1 to 5 was used to collect research data. Data were analyzed using Structural Equation Modeling-Partial Least Square (SEM-PLS) with the help of SmartPLS 4. The results showed that advertising frequency significantly and positively influenced consumer attitudes and promotions. In addition, promotions can mediate the effect of advertising frequency on consumer attitudes and have a beneficial and significant impact. These results indicate that consumer opinions towards Shopee will be more positive if advertisements are displayed more frequently and supported by appropriate promotions. This study serves as an academic reference and information source for businesses seeking to optimize social media-based digital marketing strategies.